Blood properties and protein metabolism of cows under the influence of their correction with sodium hydrohumat and propolis - Kambur, M.; Zamaziy, A.; Kasych, V. (Scientific Progress & Innovations, 2022)
Getting healthy young and high productivity from cows depends on the physiological and biochemical status of the animal's body. A significant role in this process belongs to the hemostasis system, the formation of the fetoplacental complex,and the maximum provision of the fetus with nutrients and oxygen. Studies conducted on high-yielding cows to correct hemostasis, and protein metabolism revealed the following. Different applications of humate and propolis significantly affect the content of total protein and its fractions in the blood of cows. Analyzing the options for the use of drugs in the dry period, we should note that the content of total protein in the serum of cows of the experimental group was probably higher (8.3 %) due to a slight increase in albumin content. According to our data, the total blood protein in this group of cows had a positive correlation with the level of milk productivity. In animals of the third experimental group, the total protein content did not change, but there was a tendency to increase the content of albumin and reduce globulin, both in absolute and percentage terms. Such fractional changes in the protein content in the blood of cows of both groups led to a one-way increase in the protein coefficient, more pronounced in the second group, which may be associated with increased protein synthesizing liver function. In the postpartum period, we observed a significant excess relative to the control of globulin content (g/l) in cows of the experimental groups by 32.3 %, respectively, as well as significantly lower values of serum albumin content by 24.4 % and 27.3 %. In general, it caused an insignificant increase in the total protein content after the use of propolis by 2.8 %, and in the case of humate – by 3.7 %. We found significant changes in the time of blood clot formation in cows. In cows of experimental groups, the proth rombin time of hemostasis reduced. The activation of protein-synthesizing function in the body of cows of the experimental groups may affect the indicators of hemostasis. We found similar dynamics of changes in the prothrombin hemostasis index of cows. The international normalized ratio in the cows of the experimental groups decreased by 1.13–1.16 times (p<0.05). Thrombin time of hemostasis in cows ATC in pregnant cows almost repeated the dynamics of thrombin time, decreased slightly in cows of experimental groups. Under the influence of correction, no probable increase in fibrinogen content in the blood of cows of the experimental groups was found. It is proved that the correction of hemostasis helps to increase protein metabolism in cows, maintains the physiological system of hemostasis, and creates conditions for normal growth and development of the fetus.